(untitled) (Journal of Geography and Environmental Management, 2020)
The article discusses the scientific priorities in the preparation of the new environmental education program developed by an international team of scientists and university professors, as well as employers. The priorities of research in the field of environmental science are concentrated in 17 Goals of Sustainable Development, which determine the development prospects and indicators for achieving progress in the field of ecology and society until 2030. The growing global threats associated with climate change, energy, water and food security, biodiversity conservation and ecosystem restoration require new solutions and the integration of the entire global community to train qualified specialists meeting the requirements of international education standards. Modern environmental education is an interdisciplinary system of knowledge in the field of fundamental and applied tasks in environmental research, aimed at students acquiring practical skills and competencies for the integrated solution of environmental management and sustainable development issues on a national and global scale. Analysis has been carried out the relationship of scientific environmental priorities with the mission and goals, as well as learning outcomes of the Environmental Program. Scientific and technical achievements in the field of renewable energy sources, energy and resource saving, environmentally friendly technologies in agriculture and industry became the basis for creating such courses as “Green Economy”, “Green Technologies”, “Renewable Energy”. The experience of the Reading University and Cumbria University (Great Britain) in applying scientific priorities and the achievements of modern research in the field of environmental services, forecasting the future and environmental project is used in the development of new academic disciplines and programs of educational and research practices.